2023
DOI: 10.3390/plants12091880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deep Placement Fertilization on the Distribution of Biomass, Nutrients, and Root System Development in Potato Plants

Abstract: The study was carried out in designed pots—rhizoboxes. Root systems were evaluated using computer scanning to determine total length, root area, and root diameter. The study showed a favorable effect of deep placement of fertilizers on total yield, increasing biomass yield by 7–17% relative to surface fertilization. The largest biomass increase under the influence of deep fertilization was obtained in the case of tuber yield, in which a yield increase of 18–34% was obtained. Higher yields of potato tubers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Wang et al (2019) reported a significant impact of nitrogen (N) application depth on root surface area and root volume in the 0-100 cm soil layers, with a noticeable decrease as the N depth increased. In addition, Niedziński et al (2023) indicated that deep N fertilization conditions led to an increase in crop root biomass and nutrient accumulation.…”
Section: {Insert Table 5 Here} Correlation Analysismentioning
confidence: 99%
“…Wang et al (2019) reported a significant impact of nitrogen (N) application depth on root surface area and root volume in the 0-100 cm soil layers, with a noticeable decrease as the N depth increased. In addition, Niedziński et al (2023) indicated that deep N fertilization conditions led to an increase in crop root biomass and nutrient accumulation.…”
Section: {Insert Table 5 Here} Correlation Analysismentioning
confidence: 99%
“…This is because the slow distribution of nutrients from slow-release fertilizers, combined with their deep placement, creates nitrogen and phosphorus deficiency conditions in the topsoil at the beginning of the plant growing season. Niedzinski et al [35] observed that slow-release fertilizer deep placement led to an increase in root length, accompanied by a decrease in root weight in favor of tuber yield increase. However, the results of the conducted field experiment, as shown in Table 2, indicate that the effect of fertilizer deep placement on potato tuber yields was relatively limited.…”
Section: Effect Of Fertilizer Application and Rate On Biomass Accumul...mentioning
confidence: 99%
“…Therefore, it promoted the growth, dry matter accumulation and distribution of summer maize, increased seed nitrogen and improved seed yield [5][6] . NIEDZIŃSKI T et al 7 the results showed that when the fertilization depth was 20 cm, the absorption of nitrogen and phosphorus by potato increased by 20%, and the proportion of nitrogen accumulated in tubers increased by 21%. Additionally, the length of the plant and total root area were positively affected, and these were optimal for the distribution of dry matter, nutrients, and root development parameters.…”
mentioning
confidence: 99%